Better than conscious?: the brain, the psyche, behavior, and institutions - Christoph Engel; Wolf Singer (Max Planck Institute for Research on Collective Goods, 2007)
The title of this chapter is deliberately provocative. Intuitively, many will be inclined to see conscious control of mental process as a good thing. Yet control comes at a high price. The consciously not directly controlled, automatic, parallel processing of information is not only much faster, it also handles much more information, and it does so in a qualitatively different manner. This different mental machinery is not adequate for all tasks. The human ability to consciously deliberate has evolved for good reason. But on many more tasks than one might think at first sight, intuitive decision-making, or at least an intuitive component in a more complex mental process, does indeed improve performance. This chapter presents the issue, offers concepts to understand it, discusses the effects in terms of problem solving capacity, contrasts norms for saying when this is a good thing, and points to scientific and real world audiences for this work.
Keywords: 330; Kognition; Verhaltensökonomik; Entscheidung; Theorie